Comparison between anteroposterior and oblique "Scotty dog" approach during S1 transforaminal epidural steroid injection: A randomized controlled trial. Issue 43 (23rd October 2020) - Kang, Ryung A.; Sim, Woo Seog; Choi, Ji Won; Kang, Sehee; Lee, Seungwon; Jee, Hyeon Sook; Oh, Eun Jung; Kim, Yunghun; Ko, Justin Sangwook
Abstract: Background: Traditionally, S1 transforaminal epidural steroid injection (TFESI) has been performed using an anteroposterior (AP) fluoroscopic view. In 2007, the oblique "Scotty dog" (OS) approach was introduced as an alternative technique. We compared passage time of the needle into S1 foramen (Tf ) between the anteroposterior (AP) and oblique "Scotty dog" (OS) approach during S1 TFESI. Methods: In this prospective randomized controlled trial, seventy patients scheduled S1 TFESI were randomly allocated into AP or OS groups. In the AP group, a slight cephalad-caudad tilt was used. In the OS group, the C-arm was rotated ipsilateral oblique degrees to view the S1 Scotty dog. Both groups received injection of steroid mixed with local anesthetics. We measured the passage time of the needle into S1 foramen (Tf ), primary outcome, and total procedure time (Tt ) between the groups. We also recorded presence of intravascular injection, patients-assessed pain relief for one month and complications. Results: The Tf and Tt were shorter in the OS than in the AP group (24.4 ± 24.0 s vs 47. 8 ± 53.2seconds; 93.3 ± 35.0 seconds vs 160.0 ± 98.7 seconds, P  < .001, both). Incidence of intravascular injection (AP, 8 [22.8%]; OS, 4 [11.4%], P  = .205), pain score, and complication rates were not statistically different between the two groups. In logistic regression analysis, the body mass index (BMI) was a risk factor for longer Tt (odds ratio [OR] = 1.27, 95% CI: 1.02–1.58, P  = .030). Conclusion: The passage time of the needle into S1 foramen was shorter in OS approach and the OS approach reduced the procedure time compared with the AP approach during S1 TFESI. The practitioners should note that procedure time can be prolonged in obese patients.